A time‐efficient acquisition protocol for multipurpose diffusion‐weighted microstructural imaging at 7 Tesla. Issue 6 (12th February 2017) - Sepehrband, Farshid; O'Brien, Kieran; Barth, Markus
Abstract : Purpose: Several diffusion‐weighted MRI techniques have been developed and validated during the past 2 decades. While offering various neuroanatomical inferences, these techniques differ in their proposed optimal acquisition design, preventing clinicians and researchers benefiting from all potential inference methods, particularly when limited time is available. This study reports an optimal design that enables for a time‐efficient diffusion‐weighted MRI acquisition scheme at 7 Tesla. The primary audience of this article is the typical end user, interested in diffusion‐weighted microstructural imaging at 7 Tesla. Methods: We tested b‐values in the range of 700 to 3000 s/mm 2 with different number of angular diffusion‐encoding samples, against a data‐driven "gold standard." Results: The suggested design is a protocol with b‐values of 1000 and 2500 s/mm 2, with 25 and 50 samples, uniformly distributed over two shells. We also report a range of protocols in which the results of fitting microstructural models to the diffusion‐weighted data had high correlation with the gold standard. Conclusion: We estimated minimum acquisition requirements that enable diffusion tensor imaging, higher angular resolution diffusion‐weighted imaging, neurite orientation dispersion, and density imaging and white matter tract integrity across whole brain with isotropic resolution of 1.8 mm in less than 11 min. Magn Reson Med 78:2170–2184, 2017. © 2017 International Society for Magnetic Resonance in Medicine.